1974
DOI: 10.1111/j.1751-0813.1974.tb06891.x
|View full text |Cite
|
Sign up to set email alerts
|

Cestode Parasites of the Fox in the Central Tablelands of New South Wales

Abstract: In a recent report Coman (1973) concluded that foxes play no part in the transmission of cysticercoses to domestic livestock in Victoria. This conclusion was based on a survey of 1,320 foxes examined from all parts of Victoria, in which none was found to be infected with Taenia ovis, T. hydatigena or Echinococcus gruriulmus. In contrast, Pullar (1946) had found 13.5% (9/67) and 1.2% (1167) of foxes from the Gippsland district of Victoria were infected with T . ovis and T . hydatigena respectively.A pilot surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Thus, it was concluded that foxes do not appear to be involved in the transmission of E. granulosus to domestic livestock and do not participate in the epizootiology of hydatidosis in Greece. These results are similar to those of Coman (1973a), Dent & Kelly (1974), Ryan (1976), Borgsteede (1984) and Schoffel et al (1991). On the contrary, Cook (1965) in his survey on foxes in Wales, recovered four cestode species of which only E. granulosus was mature and therefore he considered this tapeworm to be the only one transmissible by the fox.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it was concluded that foxes do not appear to be involved in the transmission of E. granulosus to domestic livestock and do not participate in the epizootiology of hydatidosis in Greece. These results are similar to those of Coman (1973a), Dent & Kelly (1974), Ryan (1976), Borgsteede (1984) and Schoffel et al (1991). On the contrary, Cook (1965) in his survey on foxes in Wales, recovered four cestode species of which only E. granulosus was mature and therefore he considered this tapeworm to be the only one transmissible by the fox.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies of the fox in Australia, involving the examination of large numbers of animals, have dealt with food habits (McIntosh 1963a;Martensz 1971 ;Coman 1973b;Ryan and Croft 1974) and with endoparasites (Pullar 1946;Coman 1973a;Dent and Kelly 1974;Ryan 1975).…”
Section: Introductionmentioning
confidence: 99%
“…In two major surveys (one each in New South Wales (NSW) and Victoria (Vic)) the intestines of over 2000 foxes were examined for helminths, although several species of taeniid cestode were recovered T. ovis and T. hydatigena were never recorded ( Coman, 1973; Ryan, 1976 ). Despite an old report of T. ovis in foxes ( Pullar, 1946 ) and a more recent report of T. hydatigena in two foxes ( Dent and Kelly, 1974 ), Coman and Ryan (1974) concluded foxes did not act as hosts for T. ovis or T. hydatigena. More recently, Howkins (1986) reported T. ovis in foxes from the Australian Capital Territory (ACT) and adjacent areas in NSW and Dybing et al (2013) reported T. hydatigena in a fox from Western Australia (WA).…”
Section: Introductionmentioning
confidence: 94%